Eriocaulon rayatianum, a new species of Eriocaulaceae from the Konkan region of Maharashtra, India - Chandore, A.n.; Borude, D.b.; Natekar, P.d.; Madhav, N.a.; Yadav, S.r. (Phytotaxa, 2019)
A new species, Eriocaulon rayatianum Chandore, Borude & S.R. Yadav, is described and illustrated from the Konkan region of Maharashtra, India. The new species is allied with E. cuspidatum Dalzell, but differs in having obovate involucral bracts, obovate to oblanceolate floral bracts, sessile male flowers and sepals and petals densely hoary in male and female flowers.